1997
DOI: 10.1128/mcb.17.7.4178
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae DNA Polymerase α Catalytic Subunit Interacts with Cdc68/Spt16 and with Pob3, a Protein Similar to an HMG1-Like Protein

Abstract: We have used DNA polymerase ␣ affinity chromatography to identify factors involved in eukaryotic DNA replication in the yeast Saccharomyces cerevisiae. Two proteins that bound to the catalytic subunit of DNA polymerase ␣ (Pol1 protein) are encoded by the essential genes CDC68/SPT16 and POB3. The binding of both proteins was enhanced when extracts lacking a previously characterized polymerase binding protein, Ctf4, were used. This finding suggests that Cdc68 and Pob3 may compete with Ctf4 for binding to Pol1. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
207
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(218 citation statements)
references
References 84 publications
11
207
0
Order By: Relevance
“…As described under "Functional Roles of FACT in DNA Replication Initiation Versus Elongation," FACT interacts with Pol␣, RPA, and the MCM complex (28,31,32) and apparently facilitates replication fork progression via its functional interaction with these replication enzymes/factors. This possibility seems to be supported by a previous study (32) that demonstrated that a point mutation introduced within a conserved surface cluster in the budding yeast Pob3-M, corresponding to the part of the Pob3 domain without the acidic region of the SSRP1 subunit of FACT (Figs.…”
Section: Are the Dna Replication Defects Observed In Ssrp1-depleted Cmentioning
confidence: 99%
“…As described under "Functional Roles of FACT in DNA Replication Initiation Versus Elongation," FACT interacts with Pol␣, RPA, and the MCM complex (28,31,32) and apparently facilitates replication fork progression via its functional interaction with these replication enzymes/factors. This possibility seems to be supported by a previous study (32) that demonstrated that a point mutation introduced within a conserved surface cluster in the budding yeast Pob3-M, corresponding to the part of the Pob3 domain without the acidic region of the SSRP1 subunit of FACT (Figs.…”
Section: Are the Dna Replication Defects Observed In Ssrp1-depleted Cmentioning
confidence: 99%
“…Nhp6 supports the function of Spt16-Pob3, a heterodimer implicated in both DNA replication and regulation of transcription (10 -12). Spt16 and Pob3 contain most of the sequences found in the components of the human FACT and frog DUF complexes (13,14), but Pob3 lacks the HMG box motif found in the otherwise homologous FACT subunit SSRP1 (12,15,16). Nhp6 appears to provide HMG box function for Spt16-Pob3 both in vivo and in vitro as cells lacking Nhp6 cannot tolerate mutations in SPT16 or POB3 (11,17), and Spt16-Pob3 can only bind to and reorganize nucleosomes in vitro if Nhp6 is present (11).…”
mentioning
confidence: 99%
“…31 In yeast, Pob3, the N-terminal counterpart of SSRP1, is also strictly required, as Pob3-null strains are not viable. 9 More precisely, as a subunit of FACT, SSRP1 appears to be critical for transcription in a wide variety of organisms, from yeast to mammals. 7 FACT is also involved in replication in yeast 9 and xenopus.…”
Section: Apoptotic Cleavage Of Ssrp1 Alters Its Association With Chromentioning
confidence: 99%
“…9 More precisely, as a subunit of FACT, SSRP1 appears to be critical for transcription in a wide variety of organisms, from yeast to mammals. 7 FACT is also involved in replication in yeast 9 and xenopus. 11 Furthermore, SSRP1 may function in more specific pathways as a coactivator for SRF and p63.…”
Section: Apoptotic Cleavage Of Ssrp1 Alters Its Association With Chromentioning
confidence: 99%
See 1 more Smart Citation